INCREASING PRODUCTION AND MARKETING OF HOME CULINARY BUSINESSES AT PINTU AIR I MEDAN BY USING SOCIAL MEDIA - Prihatin Lumbanraja; Arlina Nurbaity Lubis; Beby Kendida Hasibuan (RADJA PUBLIKA, 2024)
Micro, small and medium enterprises are one of the driving factors of the Indonesian economy. This is because this business can be carried out by all levels of Indonesian society. One of the MSME sectors that is widely used is the home catering business. This is because the food business is a business that is always in demand by consumers. The obstacles that many home businesses face are a lack of production equipment and marketing processes that are still very traditional. This activity is expected to be able to improve the production process to be more optimal and in line with consumer needs. Apart from that, this activity is also expected to be able to help partners in their marketing by using social media so that they can be better known to the wider community so that demand for products will increase.